2023
DOI: 10.1002/brb3.2948
|View full text |Cite
|
Sign up to set email alerts
|

Using functional near‐infrared spectroscopy to measure prefrontal cortex activity during dual‐task walking and navigated walking: A feasibility study

Abstract: Introduction While functional near‐infrared spectroscopy (fNIRS) can provide insight into motor‐cognitive deficits during ecologically valid gait conditions, the feasibility of using fNIRS during complex walking remains unknown. We tested the process and scientific feasibility of using an fNIRS device to measure cortical activity during complex walking tasks consisting of straight walking and navigated walking under single and dual‐task (DT) conditions. Methods Nineteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…We believe the proposed method, which seeks to increase brain activity while performing alternating finger tapping, has a double-task element. Dual tasks that involve exercise and cognitive paradigms, such as walking, activate PFC (Holtzer et al, 2011 ; Kvist et al, 2023 ), and even in older people with mild cognitive impairment, PFC activation has been observed during dual-task walking (Doi et al, 2013 ). Since the method in this study may comprise a dual-task element, brain activity is expected to increase during neurofeedback.…”
Section: Discussionmentioning
confidence: 99%
“…We believe the proposed method, which seeks to increase brain activity while performing alternating finger tapping, has a double-task element. Dual tasks that involve exercise and cognitive paradigms, such as walking, activate PFC (Holtzer et al, 2011 ; Kvist et al, 2023 ), and even in older people with mild cognitive impairment, PFC activation has been observed during dual-task walking (Doi et al, 2013 ). Since the method in this study may comprise a dual-task element, brain activity is expected to increase during neurofeedback.…”
Section: Discussionmentioning
confidence: 99%
“…This is a cross‐sectional study, referring to previous similar studies (Kvist et al., 2023 ; Salzman et al., 2021 ); we used a medium effect size of 0.3 ( f ) with a power of 0.80, alpha level of 0.05, and a correlation between repeated measures of 0.5. The power analysis indicated that a minimum of 20 participants was required.…”
Section: Methodsmentioning
confidence: 99%
“…However, environmental factors, exercise tasks, and test subjects may lead to changes in the scalp environment, probe positioning, and abnormal light-scalp coupling, which may reduce the accuracy of cerebral hemodynamic measurements [ 3 , 6 ]. Therefore, the test-retest reliability of fNIRS measurements is important.…”
Section: Introductionmentioning
confidence: 99%